Library support of university publishing at the National Technical University of Ukraine «Igor Sikorsky Kyiv Polytechnic Institute» - Druchenko, Maryna L.; Solovianenko, Denys V. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
Experience of The Scientific and Technical Library activity at the National Technical University of Ukraine “Igor Sikorsky Kyiv Polytechnic Institute” in development assistance of scientific serials of universities is presented. It was noted that “Library Publishing” model implementation enhances the partnership between the editorial periodicals of National Technical University of Ukraine “Igor Sikorsky Kyiv Polytechnic Institute”, closer alignment of the scientific serials level with international standards and improvement the Library importance in the University.